Quality and Quantity: Stormwater Management in the Alewife Brook. - Blankenship, Sara.; Holmes, Maggie.; Ledewitz, Julia.; Weaver, Samantha. (Tufts University. Tisch Library., 2018)
2011 M.A. in Urban and Environmental Policy and Planning Field Project and Water: Systems, Science and Society Practicum. Client: Mystic River Watershed Association.